2019
DOI: 10.4322/prmj.2019.003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao baixo peso ao nascer em uma maternidade pública

Abstract: Copyright Chermont et al. Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
1
0
4
Order By: Relevance
“…When birth weight was crossed with gestational age, we found that the gestational age phase that most predominated was 31 With the analysis of the length of stay in the ICU X main clinical diagnosis, an average of 27.60 days was found, although the shortest ICU time was one day and the longest was 202 days. In this case, the predominance was also of the main clinical diagnosis of PTNB with ADNPM, highlighting the great importance up to 30 days of hospitalization and even the highest admissions were of PTNB, however, the children who stayed longer in the ICU, as shown in graph 3, were those with cerebral palsy and other neurological diagnoses, when associated with these two aggravating factors.…”
Section: Resultsmentioning
confidence: 96%
“…When birth weight was crossed with gestational age, we found that the gestational age phase that most predominated was 31 With the analysis of the length of stay in the ICU X main clinical diagnosis, an average of 27.60 days was found, although the shortest ICU time was one day and the longest was 202 days. In this case, the predominance was also of the main clinical diagnosis of PTNB with ADNPM, highlighting the great importance up to 30 days of hospitalization and even the highest admissions were of PTNB, however, the children who stayed longer in the ICU, as shown in graph 3, were those with cerebral palsy and other neurological diagnoses, when associated with these two aggravating factors.…”
Section: Resultsmentioning
confidence: 96%
“…A pesquisa não teve o objetivo de avaliar a associação do RN prematuro e com baixo peso com a doença Periodontal, e sim, apresentar o perfil de puérperas que apresentaram esse desfecho. Na análise descritiva, observou-se que a idade materna principalmente entre 20 a 34 anos com a média de 26 anos, idade que corrobora com a literatura em pesquisas que avaliaram a idade materna e esses desfechos (RN prematuro e de BPN) (6,16,24).…”
Section: Resultsunclassified
“…Diferentes fatores de desencadear parto prematuro e/ou RN de BPN são estudados e associados, como: características maternas (idade materna, hábitos comportamentais, psicossociais e socioeconômicos); fatores sistêmicos, médicos e odontológicos (alteração sistêmicas, hormonais e gestacional, pré-natal, idade gestacional, saúde bucal) e fatores biológicos como infecções bacterianas (3,(6)(7)(8)(9)(10).…”
Section: Introductionunclassified
“…Acerca da relação entre prematuridade e baixo peso ao nascer, observou que 100% dos bebês que nasceram baixo peso eram prematuros, assemelhando-se com achados encontrados no trabalho realizado no Hospital no Pará, onde a prematuridade foi um fator de risco para o nascimento de RN baixo peso (CHERMONT et al, 2019). O achado desse estudo, portanto, fortalece esse modelo uma vez que os valores de GH maiores encontrados no grupo de baixo peso não se associaram com o aumento do IGF-1, como esperado em condições fisiológicas, mas não vistos quando a restrição nutricional se faz presente como descrito anteriormente.…”
Section: Discussionunclassified